Memoria y final del juego en Una noche cualquiera de Susana Torres Molina - Ruiz, Reina (Latin American Theatre Review, 2007)
Argentine playwright Susana Torres Molina presents in Una noche cualquiera (1998) a metadrama that serves as an ideological vehicle to recover Argentine memory under the military dictatorship during the period of la guerra sucia (1976-1983). Democracy has not yet lawfully solved the atrocities of that time. The play portrays the frustration and pain of some individuals who, tired of waiting for justice, are ready to take it into their hands. Through role-playing, the leading characters perform a series of games to make their victims confess hidden truths about their past. Illicit methods are used including psychological torture, violent threats, verbal abuse, etc. but at the end, the desired sense of personal closure is achieved. (RR, Article in Spanish)